(untitled) (Colombia Medica, 2010)
Introduction: Epiphyseal dysplasia of the femoral head (EDFH) is defined as an alteration in the development of the child’s hip, characterized by delayed ossification of the proximal femoral epiphysis. Methods: Herein, we present six cases of epiphyseal dysplasia of the femoral head (EDFH), seen by the principal author (EVA) within the last six years with minimum follow up at 15 months. Results: The cases were all diagnosed as casual findings. None of the children had symptoms or clinical signs in the hip, only one had a history of hip pain for five days, two months prior, which was diagnosed at the time as transient synovitis. Discussion: Among the differential diagnoses, the main one is Perthes disease, which is differentiated by several parameters like earlier age onset for EDFH (in children below 4 years of age), bilateralism (50% vs. 10%), and a calmer presentation in Meyer’s dysplasia. The evolution in Meyer’s dysplasia is toward improving radiographic changes. None of the patients revealed incongruence of the hip or early degenerative changes, indicating an excellent prognosis. Many authors think it is a variant of the normal ossification of the femoral head.